SOME GAME-THEORETICAL MODELS OF INFORMATION SECURITY PROBLEMS - Saghatelyan, K. V.; Tairyan, V. I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
In the present paper the game models of information security are considered. A few formulations of information security problems are introduced and quite simple game models are built. Specific solutions of several matrix games and a duel type games are derived.